P4HA1: an important target for treating fibrosis related diseases and cancer - Yang, Xuewen; Zhang, Dong; Li, Mengmeng; Shao, Yingchun; Zhang, Xiyang; Xue, Yongzhi (Frontiers in Pharmacology, 2024)
Fibrosis is significantly associated with a wide variety of diseases and is involved in their progression. Fibrosis activated under the influence of different combinations of factors is considered a double-edged sword. Although there has been much research on organ fibrosis in recent years, a variety of organ fibrosis diseases and cancers are not well controlled in terms of prevention, treatment, and prognosis. Clinical studies still lack exploration and discovery of effective targets for the pathogenesis of organ fibrosis. Prolyl 4-hydroxylase subunit alpha 1 (P4HA1) is a protein kinase and the synthesis and secretion of collagen are related to the sustained activation of P4HA1. As further studies are being conducted,  the potential role of P4HA1 in the development of fibrosis-associated diseases and cancer is becoming clear. Consequently, we conducted a systematic review and discussion on the role of P4HA1 in the pathogenesis of various fibrosis-related diseases and cancers. We reviewed the possible strategies of P4HA1 in the diagnosis and treatment of fibrosis-related diseases and cancers, and analyzed its potential relevance as a biomarker in the diagnosis and treatment of fibrosis-related diseases and cancer.